Enhancing Broiler Feed Market Share in Jabodetabek: An Importance–Performance Analysis Approach - Fuad Dudin; Rahayu Widiyanti; Titin Widyastuti; Novie Andri Setianto; Ismoyowati (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2026)
This study aims to formulate a market share enhancement strategy for broiler feed in the Jabodetabek region using Importance-Performance Analysis (IPA). A survey was conducted with 68 PT NH customers in the Jabodetabek region as respondents. Data were analyzed using descriptive statistics and IPA. The results indicated that competitive pricing (Gap: +1.25), distribution availability (Gap: +1.20), and feed variety (Gap: +0.51) were the key priority attributes requiring improvement. In contrast, after-sales service, feed quality, and nutritional content were in the